How do midwives in Slovenia view their professional status?. Issue 12 (December 2015) - Mivšek, Polona; Pahor, Majda; Hlebec, Valentina; Hundley, Vanora
Abstract: Objective: the aim of the study was to explore Slovenian midwives' views of their professional status. The influence of participants' educational background on their views was also examined, since higher education is related to professionalism. Design: this was a quantitative descriptive survey, using postal data collection. The questionnaire comprised of six elements crucial for professionalism – three elements distinctive of 'old' professionalism (power, ethics, specific knowledge) and three characteristics of 'new' professionalism (reflective practice, inter-professional collaboration and partnership with users). Participants: a total of 300 midwives who were registered in a national register of nurses and midwives at the time of the study. The response rate was 50.7% (152 returned the questionnaire). Participants that were on a probationary period were excluded, leaving 128 questionnaires for analysis (43%). Some 40.9% participants had secondary midwifery education, 56.7% had higher midwifery education and only few (2.4%) finished postgraduate education. Findings: the majority of participants did not consider midwifery to be a specific profession. Midwives with secondary education were more likely to consider practical skills to be important than theoretical midwifery knowledge. In general midwives did not feel enabled to practice autonomously; and this caused them to face ethical dilemmas when aiming to fulfil women's wishes. All participants with midwifery secondary school education thought that obstetrics jeopardises midwifery scope of practice, but only half of the BSc participants thought this. One-fifth of all participants estimated that midwifery is also threatened by nursing. The respondents reported feeling a lack of control over their professional activity and policy making; however the majority of midwives claimed that they were willing to take on more responsibility for independent practice. Key conclusions: Slovenian midwifery cannot be considered to be a profession yet. It faces several hindrances, due to its historical development. Implications for practice: in order to develop a specific professional identity for midwives, the content and structure of education should be analysed and changed in order to improve socialisation and professionalism. In clinical settings, the scope of midwifery practice and responsibilities, as defined by EU directives, should be agreed by all professional groups. Highlights: An association between higher degrees and a rise in professionalism was confirmed. In our study the majority of the participants did not see midwifery as a specific expertise. Lack of autonomy was frequently exposed by the participants.